Low polymerization degree acrylic acid modified composite alcohol amine cement grinding aid and preparation method thereof

CN123003772APending Publication Date: 2026-10-30YIYU INTELLIGENT MATERIALS (SICHUAN) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219556.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]然而,传统的单一醇胺类助磨剂存在以下不足:一方面,三乙醇胺价格较高,导致助磨剂成本居高不下;另一方面,单一醇胺难以同时兼顾粉磨过程中的助磨效果和水泥水化过程中的强度发展

Benefits of technology

1.助磨效率高:本发明利用低聚合度聚丙烯酸与己酸的协同作用,通过与复合醇胺的酯化反应,制备出含有多个活性基团的复合助磨剂分子。其助磨机理为:酯化反应生成的产物分子中保留了一定数量的未反应羧基,该羧基在水泥浆体的碱性环境中解离为羧酸根,吸附于带正电的水泥颗粒表面,通过静电排斥力有效分散水泥颗粒,破坏颗粒团聚。同时,产物分子中引入的醇胺酯基团和未反应的醇胺羟基具有助磨功能,可进一步降低颗粒表面能。羧酸基团和醇胺基团在同一分子内协同作用,使助磨效率较单一醇胺显著提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a low-polymerization-degree acrylic acid modified composite alcohol amine cement grinding aid and a preparation method thereof, and belongs to the technical field of cement additives. The method comprises the following steps: preparing a mixed acid by compounding low-polymerization-degree polyacrylic acid with a molecular weight of 400-600 and hexanoic acid at a mass ratio of 3:7, compounding mixed alcohol amine by compounding triisopropanol amine and diethanol monoisopropanol amine at a mass ratio of 2:8-5:5, and performing esterification reaction on the mixed acid and the mixed alcohol amine under the catalysis of sulfuric acid at 85 DEG C for 4-6 hours while vacuumizing and removing water, so as to prepare the composite alcohol amine cement grinding aid. The prepared grinding aid has the advantages of high grinding efficiency, high early strength of cement, good compatibility with concrete admixtures and the like, and has a wide industrial application prospect due to simple production process and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement additives, specifically to a low-polymerization-degree acrylic acid-modified composite amine cement grinding aid and its preparation method. Background Technology

[0002] Cement grinding aids are chemical additives used in the cement grinding process to significantly improve grinding efficiency and reduce energy consumption. In cement production, the grinding process accounts for 60% to 70% of total energy consumption; therefore, improving grinding efficiency and reducing grinding energy consumption are of great significance for energy conservation and emission reduction in the cement industry.

[0003] Alkanolamines are the core active components in cement grinding aids, with triethanolamine (TEA) and triisopropanolamine (TIPA) being the most widely used. Alkanolamine grinding aids improve grinding efficiency by adsorbing onto the surface of cement particles, neutralizing the surface charge, and reducing electrostatic agglomeration between particles. Furthermore, alkanolamines can also undergo complexation reactions with the aluminate phase (C3A) in cement, promoting cement hydration and improving the early strength of the cement.

[0004] However, traditional single-alcoholic amine grinding aids have the following shortcomings: on the one hand, triethanolamine is expensive, resulting in high grinding aid costs; on the other hand, single-alcoholic amines are difficult to simultaneously achieve both grinding aid effect during the grinding process and strength development during cement hydration.

[0005] In recent years, the preparation of modified alkanolamine grinding aids by esterification of organic acids with alkanolamines has become a research hotspot. Existing technologies include esterification modifications of organic acids such as citric acid and acetic acid with triethanolamine, but these methods still suffer from high raw material costs and a narrow range of product applicability.

[0006] Polyacrylic acid is a commonly used polymer dispersant. Low-polymerization-degree polyacrylic acid has shorter molecular chains, lower viscosity, and better water solubility. Under alkaline conditions, the carboxyl groups on its molecular chains can dissociate into carboxylate groups, which are then adsorbed onto the surface of cement particles via electrostatic attraction, achieving dispersion. Simultaneously, the smaller molecular weight of low-polymerization-degree polyacrylic acid allows it to form esterified products with suitable molecular weights after esterification with alkanolamines. This process retains the dispersing ability of the carboxyl groups while introducing the grinding-aiding and hydration-promoting functions of alkanolamines. Furthermore, hexanoic acid, a short-chain saturated fatty acid, is inexpensive, has a short carbon chain, and low steric hindrance. Combining it with low-polymerization-degree polyacrylic acid is expected to reduce raw material costs while maintaining grinding-aiding effects.

[0007] Therefore, developing a method for preparing cement grinding aids by esterification reaction of low-polymerization-degree polyacrylic acid and hexanoic acid as mixed acid raw materials with composite alkanolamines is of great significance for promoting the advancement of cement grinding aid technology. Summary of the Invention

[0008] To address the aforementioned technical problems, the purpose of this invention is to provide a low-polymerization degree acrylic acid-modified composite alkanolamine cement grinding aid and its preparation method, which has high grinding efficiency, significantly improves the early strength of cement, has good compatibility with concrete admixtures, and is low in cost.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, this invention provides a method for preparing a low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid, comprising the following steps: Step 1: Mix low-polymerization degree polyacrylic acid and hexanoic acid at a mass ratio of 3:7 to prepare a mixed acid; wherein the molecular weight of the low-polymerization degree polyacrylic acid is 400~600. Step 2: Mix triisopropanolamine and diethanol monoisopropanolamine at a mass ratio of 2:8 to 5:5 to prepare a mixed alcoholamine; Step 3: Add the mixed acid obtained in Step 1, the mixed alkanolamine obtained in Step 2, and the catalyst sulfuric acid to the reactor at a mass ratio of 1:1:0.01. React at 83~87℃ for 4~6 hours, while applying vacuum to remove the water generated in the reaction, to obtain low-polymerization degree acrylic acid modified composite alkanolamine cement grinding aid.

[0010] Furthermore, in step 1, the molecular weight of the low-polymerization-degree polyacrylic acid is 450~550.

[0011] Furthermore, in step 2, the mass ratio of triisopropanolamine to diethanol monoisopropanolamine is 3:7 to 4:6.

[0012] Furthermore, in step 3, the reaction time is 5-6 hours, and the reactor is a double-necked glass reactor.

[0013] Furthermore, in step 3, the vacuum level after applying the vacuum is -0.08 to -0.10 MPa.

[0014] Further, in step 1, the low-polymerization degree polyacrylic acid and hexanoic acid are mixed and stirred at room temperature at a stirring speed of 60~120 rpm for 20~40 minutes.

[0015] Furthermore, in step 2, triisopropanolamine and diethanol monoisopropanolamine are mixed and stirred at room temperature at a stirring speed of 40-80 rpm for 15-30 minutes.

[0016] Furthermore, in step 3, the catalyst sulfuric acid is sulfuric acid with a mass fraction of 98%.

[0017] In a second aspect, the present invention provides a low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid prepared by the above method.

[0018] In a third aspect, the present invention provides an application of the low-polymerization-degree acrylic acid modified composite amine cement grinding aid as described above, wherein the dosage of the cement grinding aid in the cement grinding process is 0.01% to 0.05% of the cement mass.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. High Grinding Efficiency: This invention utilizes the synergistic effect of low-polymerization-degree polyacrylic acid and hexanoic acid to prepare a composite grinding aid molecule containing multiple active groups through esterification with a composite alkanolamine. The grinding mechanism is as follows: the product molecule generated by the esterification reaction retains a certain number of unreacted carboxyl groups. These carboxyl groups dissociate into carboxylate groups in the alkaline environment of cement paste, adsorbing onto the surface of positively charged cement particles. Through electrostatic repulsion, the cement particles are effectively dispersed, breaking particle agglomeration. Simultaneously, the alkanolamine ester groups and unreacted alkanolamine hydroxyl groups introduced into the product molecule have grinding-aiding functions, further reducing particle surface energy. The synergistic effect of the carboxylate and alkanolamine groups within the same molecule significantly improves the grinding efficiency compared to a single alkanolamine.

[0020] 2. High Early Strength of Cement: The triisopropanolamine and diethanol monoisopropanolamine components in the grinding aid prepared in this invention can promote the hydration reaction of the silicate and aluminate phases in cement. Specifically, the three hydroxyl groups in the triisopropanolamine molecule can undergo a complexation reaction with tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF) in cement, promoting the hydration of the aluminate phase and generating ettringite (AFt) and monosulfide-type hydrated calcium sulfoaluminate (AFm), thus accelerating the development of early strength. Diethanol monoisopropanolamine promotes the hydration of tricalcium silicate (C3S) and accelerates the formation rate of CSH gel. The combination of the two components achieves synergistic activation of different mineral phases in cement, significantly improving the 3-day and 28-day compressive strength of cement.

[0021] 3. Good compatibility with concrete admixtures: This invention uses low-polymerization-degree polyacrylic acid (molecular weight 400-600) as raw material, and the product after esterification has a moderate molecular weight. When traditional high-molecular-weight polycarboxylic acid substances (molecular weight tens of thousands to hundreds of thousands) coexist with concrete water-reducing agents (especially polycarboxylic acid water-reducing agents), the carboxyl groups on the high-molecular-weight polyacrylic acid chain and the carboxyl groups on the polycarboxylic acid water-reducing agent molecular chain will compete for adsorption on the surface of cement particles, resulting in competitive adsorption and a decrease in the actual adsorption capacity and a poorer dispersion effect of the water-reducing agent. The product obtained by this invention has a much lower molecular weight than polycarboxylic acid water-reducing agents and will not compete for adsorption with water-reducing agent molecules on the surface of cement particles, thus exhibiting good compatibility.

[0022] 4. Low cost: In this invention, hexanoic acid accounts for 70% of the mixed acids. As a bulk industrial raw material, hexanoic acid is much cheaper than traditional grinding aid raw materials such as triisopropanolamine. In addition, the combined use of triisopropanolamine and diethanol monoisopropanolamine is more cost-effective than triethanolamine alone. At the same time, the grinding efficiency per unit mass of product is improved through esterification modification, resulting in a significant reduction in overall cost.

[0023] 5. Simple production process: This invention adopts a one-step esterification method with mild reaction conditions (85℃, vacuum degree -0.08~-0.10MPa), which does not require high-pressure equipment or complex temperature control systems. It has low requirements for production equipment, short process flow, and is easy to realize large-scale industrial production.

[0024] 6. Stable Product Quality: This invention promotes the forward esterification reaction by removing water through vacuum. Esterification is a reversible reaction; if the water generated in the reaction is not removed in time, it will inhibit the reaction from proceeding in the forward direction. By continuously applying a vacuum (-0.08~-0.10MPa), the partial pressure of water in the system is reduced, causing water to be continuously extracted from the reaction system. According to Le Chatelier's principle, the equilibrium shifts towards the esterification product. Under these conditions, the reaction conversion rate can reach over 95%. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0026] All raw materials used in the embodiments of this invention are commercially available products, as detailed below: Low degree of polymerization polyacrylic acid: molecular weight 400~600, industrial grade, commercially available product; Hexanoic acid: Industrial grade, purity ≥99%, commercially available product; Triisopropanolamine (TIPA): Industrial grade, purity ≥85%, commercially available product; Diethanol monoisopropanolamine (DEIPA): Industrial grade, purity ≥90%, commercially available product; Catalyst sulfuric acid: 98% sulfuric acid, analytical grade, commercially available product.

[0027] The performance testing method in this embodiment of the invention is as follows: (1) Grinding efficiency test: The test was conducted according to GB / T 26748-2011 "Cement Grinding Aid". 95% by mass of cement clinker and 5% by mass of gypsum were mixed (total mass of 100%, i.e., the total mass of cement obtained after grinding) and added to the test mill. The grinding aid of the present invention (Examples 1-3) and the comparative grinding aid, accounting for 0.03% of the total mass of cement, were added respectively. A standard test mill with a diameter of 500mm×500mm was used. The total mass of the material fed into the mill was 5kg and the total mass of the grinding media was 100kg. Each group was ground for 30min under the same grinding conditions. The specific surface area of ​​the cement after grinding (Bligh method, refer to GB / T 8074) and the residue on a 45μm sieve (refer to GB / T 1345) were measured. The increase in specific surface area and the decrease in residue on the sieve were used to characterize the grinding efficiency.

[0028] (2) Cement strength test: The test was conducted in accordance with GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)". The compressive strength of cement after adding grinding aid was measured at 3 days and 28 days, and compared with the blank sample (cement without grinding aid) to calculate the strength improvement value.

[0029] (3) Compatibility test with water-reducing agent: The grinding aid of the present invention and the polycarboxylate water-reducing agent were compounded at a mass ratio of 1:8 and added to cement paste (a paste made of cement and water) (the grinding aid dosage was 0.03% of the cement mass, the polycarboxylate water-reducing agent dosage was 0.24% of the cement mass, and the water-cement ratio was 0.29). The initial fluidity and fluidity loss after 60 minutes were tested according to GB / T 8077 "Test method for homogeneity of concrete admixtures".

[0030] (4) Esterification conversion rate determination: The conversion rate was determined by a combination of acid value titration and ¹H-NMR nuclear magnetic resonance quantification.

[0031] Acid value titration method: Referring to GB / T 1668-2008 "Determination of Acid Value and Acidity of Plasticizers", the acid values ​​of the mixed acid before esterification and the product after esterification were determined using a standard sodium hydroxide titration solution. The esterification conversion rate was calculated using the following formula: Esterification conversion rate = (acid value before reaction - acid value after reaction) / acid value before reaction × 100%.

[0032] ¹H-NMR quantitative calibration: The results obtained by the acid value titration method were further calibrated and verified using the ¹H-NMR quantitative method.

[0033] The specific method is as follows: using deuterated dimethyl sulfoxide (DMSO-d5) as solvent, the mixed acid sample before the esterification reaction was taken and the reaction was terminated by low-temperature quenching. A small amount of sample was directly dissolved to avoid further reaction of the product due to heating. Three sets of data were obtained by integrating the ¹H-NMR spectrum: ① total molar amount of hexanoic acid (calculated by the integrated area of ​​the characteristic peak of the ortho-methylene hydrogen of the hexanoic acid carboxyl group); ② total molar amount of polyacrylic acid structural units (calculated by the integrated area of ​​the methylene hydrogen of the polyacrylic acid main chain); ③ molar amount of unreacted hydroxyl groups (calculated by the integrated area of ​​the characteristic peak of the hydroxyl hydrogen of the alkanolamine). The esterification conversion rate was directly calculated from the amount of hydroxyl group consumed (1 mol of hydroxyl group consumption ≈ 1 mol of carboxyl group esterification), specifically calculated by the following formula: ; in, X For esterification conversion rate, n 初始OH This represents the total number of moles of hydroxyl groups in the mixed alkanolamines before the reaction. n 剩余OH This represents the number of unreacted hydroxyl groups in the product after the reaction.

[0034] The conversion rate measured by acid value titration was compared and calibrated using ¹H-NMR quantitative results to confirm the consistency of the results of the two methods (error ≤2%).

[0035] Example 1, as a preferred embodiment of the present invention, the preparation method of this embodiment is as follows: Step 1, Preparation of mixed acid: Mix low-polymerization degree polyacrylic acid with a molecular weight of 500 with hexanoic acid at a mass ratio of 3:7, and stir at 80 rpm for 30 minutes at room temperature to obtain mixed acid.

[0036] Step 2, Preparation of mixed alcoholamines: Triisopropanolamine and diethanol monoisopropanolamine are mixed at a mass ratio of 3:7 and stirred at 60 rpm for 20 minutes at room temperature to obtain mixed alcoholamines.

[0037] Step 3, esterification reaction: Mixed acid, mixed alkanolamine, and sulfuric acid catalyst are added to a double-necked glass reactor at a mass ratio of 1:1:0.01. The temperature is raised to 85°C, a vacuum of -0.09 MPa is applied, and the reaction is carried out for 5 hours while continuously removing the generated moisture under vacuum. After the reaction is completed, the temperature is lowered to room temperature to obtain a low-polymerization degree acrylic acid-modified composite alkanolamine cement grinding aid.

[0038] The grinding aid was added to cement at 0.03% of the cement mass during grinding. Test results showed that compared with the blank sample, the specific surface area of ​​the cement increased by 12.5%, the residue on the 45μm sieve decreased by 2.8 percentage points, the 3-day compressive strength increased by 3.2 MPa, and the 28-day compressive strength increased by 4.5 MPa. The esterification conversion rate of the product in this embodiment was determined to be 95.8%.

[0039] Example 2, as a preferred embodiment of the present invention, the preparation method of this embodiment is as follows: Step 1, Preparation of mixed acid: Low-polymer polyacrylic acid with a molecular weight of 450 is mixed with hexanoic acid at a mass ratio of 3:7 and stirred at 100 rpm for 25 minutes at room temperature to obtain mixed acid.

[0040] Step 2, Preparation of mixed alcoholamines: Triisopropanolamine and diethanol monoisopropanolamine are mixed at a mass ratio of 2:8 and stirred at 50 rpm for 25 minutes at room temperature to obtain mixed alcoholamines.

[0041] Step 3, esterification reaction: Mixed acid, mixed alkanolamine, and sulfuric acid catalyst are added to a double-necked glass reactor at a mass ratio of 1:1:0.01. The temperature is raised to 85°C, a vacuum of -0.08 MPa is applied, and the reaction is carried out for 6 hours while continuously removing the generated moisture under vacuum. After the reaction is completed, the temperature is lowered to room temperature to obtain a low-polymerization degree acrylic acid-modified composite alkanolamine cement grinding aid.

[0042] The grinding aid was added to cement at 0.03% of the cement mass for grinding. Test results showed that compared with the blank sample, the specific surface area of ​​the cement increased by 11.8%, the residue on the 45μm sieve decreased by 2.6 percentage points, the 3-day compressive strength increased by 2.9 MPa, and the 28-day compressive strength increased by 4.1 MPa. The esterification conversion rate of the product in this embodiment was determined to be 96.3%.

[0043] Example 3, as a preferred embodiment of the present invention, the preparation method of this embodiment is as follows: Step 1, Preparation of mixed acid: Low degree of polymerization polyacrylic acid with a molecular weight of 550 is mixed with hexanoic acid at a mass ratio of 3:7 and stirred at 120 rpm for 20 minutes at room temperature to obtain mixed acid.

[0044] Step 2, Preparation of mixed alcoholamines: Triisopropanolamine and diethanol monoisopropanolamine are mixed at a mass ratio of 4:6 and stirred at 70 rpm for 15 minutes at room temperature to obtain mixed alcoholamines.

[0045] Step 3, esterification reaction: Mixed acid, mixed alkanolamine, and sulfuric acid catalyst are added to a double-necked glass reactor at a mass ratio of 1:1:0.01. The temperature is raised to 85°C, a vacuum of -0.10 MPa is applied, and the reaction is carried out for 4 hours while continuously removing the generated moisture under vacuum. After the reaction is completed, the temperature is lowered to room temperature to obtain a low-polymerization degree acrylic acid-modified composite alkanolamine cement grinding aid.

[0046] The grinding aid was added to cement at 0.03% of the cement mass during grinding. Test results showed that compared with the blank sample, the specific surface area of ​​the cement increased by 13.1%, the residue on the 45μm sieve decreased by 3.0 percentage points, the 3-day compressive strength increased by 3.5 MPa, and the 28-day compressive strength increased by 4.8 MPa. The esterification conversion rate of the product in this embodiment was determined to be 95.4%.

[0047] Comparative Example 1 used commercially available triethanolamine (TEA, purity ≥85%) as a grinding aid, at a dosage of 0.03% of the cement mass. Test results showed that compared to the blank sample, the cement specific surface area increased by 8.2%, the 45μm sieve residue decreased by 1.8 percentage points, the 3-day compressive strength increased by 2.1 MPa, and the 28-day compressive strength increased by 3.0 MPa. All of these indicators were lower than those in Examples 1-3 of this invention.

[0048] Comparative Example 2 differs from Example 1 only in that: hexanoic acid is not added in step 1, that is, low-polymerization degree polyacrylic acid is used alone to carry out the esterification reaction with the composite alcohol amine, and the remaining components and operations are the same as in Example 1.

[0049] The admixture dosage was 0.03% of the cement mass. Test results showed that compared with the blank sample, the specific surface area of ​​the cement increased by 10.4%, the residue on the 45μm sieve decreased by 2.3 percentage points, the 3-day compressive strength increased by 2.6 MPa, and the 28-day compressive strength increased by 3.7 MPa.

[0050] Comparative Example 3 differs from Example 1 only in that the esterification reaction (step 3) is not performed; that is, the mixed acid obtained in step 1 and the mixed alkanolamine obtained in step 2 are directly and physically mixed at room temperature in the same mass ratio. The remaining components and operations are the same as in Example 1.

[0051] The admixture dosage was 0.03% of the cement mass. Test results showed that compared with the blank sample, the specific surface area of ​​the cement increased by 9.1%, the residue on the 45μm sieve decreased by 2.0 percentage points, the 3-day compressive strength increased by 2.3 MPa, and the 28-day compressive strength increased by 3.3 MPa.

[0052] The esterification conversion rates of the grinding aids prepared in Examples 1-3 were determined by acid value titration to be 95.8%, 96.3%, and 95.4%, respectively. The results were consistent with those obtained by ¹H-NMR quantitative nuclear magnetic resonance (error ≤2%), indicating that the product quality is stable and controllable between batches.

[0053] The test results of each embodiment and comparative example are summarized in Table 1.

[0054] Table 1 Summary of Test Results

[0055] As shown in Table 1, compared with Comparative Example 1 (8.2%, 1.8%, 2.1 MPa, 3.0 MPa, 225 mm), the grinding aids of Examples 1-3 are significantly superior to commercially available triethanolamine (TEA) grinding aids in terms of increased specific surface area (11.8%-13.1%), reduced 45 μm sieve residue (2.6-3.0%), increased 3-day strength (2.9-3.5 MPa), increased 28-day strength (4.1-4.8 MPa), and initial flowability of the paste when compounded with the water-reducing agent (240-250 mm). This indicates that the molecular structure design of the esterification product and the synergistic effect of the carboxyl-amino groups have significant advantages. Furthermore, the flowability loss of Examples 1-3 over 60 minutes was less than that of Comparative Example 1, further demonstrating the good compatibility of the grinding aids of this invention with the polycarboxylate superplasticizer.

[0056] Comparing Example 1 and Comparative Example 2, it can be seen that after adding hexanoic acid, the specific surface area of ​​the grinding aid increased from 10.4% to 12.5%, the reduction in 45μm sieve residue increased from 2.3% to 2.8%, the 3-day and 28-day compressive strength increased from 2.6MPa and 3.7MPa to 3.2MPa and 4.5MPa, respectively, and the initial flowability of the cement paste increased from 238mm to 245mm. This indicates that the combination of hexanoic acid and low-polymerization-degree polyacrylic acid has a synergistic effect: the short carbon chain and low steric hindrance of hexanoic acid molecules make it easier for its esterification products to form a uniform adsorption layer on the surface of cement particles, which complements the electrostatic dispersion effect of polyacrylic acid esterification products, thereby further improving the grinding aid efficiency and strength development level.

[0057] A comparison of Example 1 and Comparative Example 3 shows that Comparative Example 3, which involved the physical mixing of mixed acids and mixed alkanolamines without esterification, exhibited significantly lower performance in all aspects compared to Example 1 (9.1% increase in specific surface area, 2.0 percentage point decrease in 45 μm sieve residue, 2.3 MPa increase in 3-day strength, 3.3 MPa increase in 28-day strength, and 230 mm initial flowability of the paste). This indicates that esterification is a crucial step in achieving the intramolecular synergistic effect between carboxyl and alkanolamine groups: the esterification product integrates the electrostatic dispersion function of carboxyl groups with the grinding aid and hydration-promoting functions of alkanolamines into the same molecule, resulting in a significantly better overall effect than the simple physical superposition of the components.

[0058] The method for preparing low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid provided by this invention utilizes readily available and widely sourced raw materials, employs mild reaction conditions, and requires minimal equipment, making it suitable for large-scale industrial production. The prepared grinding aid can be widely applied in various cement grinding processes, significantly improving cement grinding efficiency, reducing grinding energy consumption, and enhancing cement product performance, demonstrating promising industrial application prospects and economic benefits.

[0059] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid, characterized in that, Includes the following steps: Step 1: Mix low-polymerization degree polyacrylic acid and hexanoic acid at a mass ratio of 3:7 to prepare a mixed acid; wherein the molecular weight of the low-polymerization degree polyacrylic acid is 400~600. Step 2: Mix triisopropanolamine and diethanol monoisopropanolamine at a mass ratio of 2:8 to 5:5 to prepare a mixed alcoholamine; Step 3: Add the mixed acid obtained in Step 1, the mixed alkanolamine obtained in Step 2, and the catalyst sulfuric acid to the reactor at a mass ratio of 1:1:0.

01. React at 83~87℃ for 4~6 hours, while applying vacuum to remove the water generated in the reaction, to obtain low-polymerization degree acrylic acid modified composite alkanolamine cement grinding aid.

2. The preparation method according to claim 1, characterized in that, In step 1, the molecular weight of the low-polymerization degree polyacrylic acid is 450~550.

3. The preparation method according to claim 1, characterized in that, In step 2, the mass ratio of triisopropanolamine to diethanol monoisopropanolamine is 3:7 to 4:

6.

4. The preparation method according to claim 1, characterized in that, In step 3, the reaction time is 5-6 hours, and the reactor is a double-necked glass reactor.

5. The preparation method according to claim 1, characterized in that, In step 3, the vacuum level after applying the vacuum is -0.08 to -0.10 MPa.

6. The preparation method according to claim 1, characterized in that, In step 1, low-polymerization-degree polyacrylic acid and hexanoic acid are mixed and stirred at room temperature at a stirring speed of 60~120 rpm for 20~40 minutes.

7. The preparation method according to claim 1, characterized in that, In step 2, triisopropanolamine and diethanol monoisopropanolamine are mixed and stirred at room temperature at a stirring speed of 40-80 rpm for 15-30 minutes.

8. The preparation method according to claim 1, characterized in that, In step 3, the catalyst sulfuric acid is sulfuric acid with a mass fraction of 98%.

9. A low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid prepared by the method according to any one of claims 1 to 8.

10. The application of the low-polymerization-degree acrylic acid-modified composite alkanolamine cement grinding aid as described in claim 9, characterized in that, The dosage of cement grinding aid in the cement grinding process is 0.01% to 0.05% of the cement mass.